Gender Mainstreaming in Slum-Free City Program (KOTAKU) in Kalegowa Village, Gowa Regency - Fatimah; Suparman; Arsyad; Sakaruddin Mandjarreki; Helmy Ayuradi Miharja (LPPM IAIN Parepare, 2026)
Gender mainstreaming is a key principle of community-based development, yet previous studies have primarily viewed women as indicators of participation rather than examining how gender mainstreaming strengthens their capacity, representation, and influence in community governance. This study analyses gender mainstreaming strategies in the Slum-Free City Program (KOTAKU) in Kalegowa Village, Gowa Regency, using a descriptive qualitative approach. Data were collected through in-depth interviews, observation, and document analysis involving nine purposively selected informants and analysed using interactive analysis with triangulation. The findings identify four interconnected strategies: strengthening gender awareness, enhancing women's capacity, expanding women's participation in community institutions, and increasing their engagement in socio-economic activities. Their effectiveness depends on inclusive policies, continuous socialisation, and growing community acceptance of women's leadership. The study concludes that gender mainstreaming functions not only as an administrative tool but also as a mechanism of social transformation that strengthens women's bargaining power and enables their substantive influence in community decision-making.